BUKU ILUSTRASI “FASHION AND STYLE GUIDE” - ANGELA DIOS, Drs. Syafwan, M.Si., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Knowledge in fashion style is still uncommon by most women, meanwhile guidance in ashion is still difficult to find especially one with pictures. Therefore it is needed to ompose book as a style guidance. Fashion and Style Guide’s book is devided in to two sections, that are fashion dictionary and style guide that is consist of guidance and tipsin fashion. This book is filled with attractive watercolor illustrations to create a better understanding for the readers. The objective of composing this book is to upscale the elfconfindence of women in wearing their clothes. 5W +1H analysis is used in finding the solution in composing the book. Literature study is done to complete the verbal content from target audience. The result of the study is written in simple and attractive language. Supporting media such as e-poster, Ig ccount, mini journal, notebook, pin, stickers is created to support the book existence.Keyword : Book, fashion, style, illustration.